Ang binibining tumalo sa mahal na hari - Reyes, Severino O.; Bellen, Christine S.; Or, Elbert (Mandaluyong City : Anvil Publishing, 2005)
A retelling of the story about a wise and courageous maiden who was able to carry out all of the challenges given to her by the king.
Keywords: Courage -- Juvenile fiction; Children's stories, Filipino